Peningkatan Motivasi Siswa dalam Belajar Kosa kata dengan Menggunakan Video Buatan Sendiri di SMP 1 Muara Bungo - Sri wahyuni (Universitas Muhammadiyah Muara Bungo, 2019)
This research aims at find out the improvement of students’ learning vocabulary by using self made song. The method of this research was classroom action research (CAR) which consisted of planing, actioning, observing and reflecting. The data of this research will be analyzed by using two methods of data analysis. Quantitative data analysis used to examine and interprete data from task and speaking test. The data taken from observation, field note and interview will be analyzed by using qualitative data analysis. Teaching vocabulary through song gave more positive effect for improving students’ motivation in learning English. The technique will gives different learning experience for the students, establishes students’ confidence, makes the students interest in English class, reduces their anxiety, and makes them more happily. It expected proved that students’ song is more effective than conventional method. By applying this song, theteacher suppose can be more creative in updating the learning in order to produce a better result in English learning achievement especially vocabulary. Besides that, song can make the teaching and learning process more fun and enjoyable.